The Role of the DPYD Test in Managing a Successful Response to the Covid Pandemic - Allazov Iskandar Salakh ogli (Journal of Science in Medicine and Life, 2024)
This article is devoted to the topic COVID-19, which describes ways to determine the levels of morbidity and infestation of COVID-19 in. The article presents the current epidemiological indicators of COVID-19 coronavirus infection. Clinical manifestations and risk factors of this infection were noted. The current situation in the world.